Using media-psychological technologies to form tolerant attitude towards children with disabilities in pedagogical specialists in the process of their professional training in Ukraine - Subashkevych, Iryna; Korniat, Vira (Special Education, 2020)
The article deals with the problem of the formation of a tolerant attitude towards children with disabilities in students of pedagogical specialties during their professional training. It is noted that in the contextof the development of inclusive education in Ukraine, it is important to improve the educational process of the higher education institutions in order to train competent staff ready to work with children with disabilities. The level of tolerance formed in students of pedagogical specialties is analysed. The system of working with students using media-psychological technologies and media resources in the learning process is proposed; the effectiveness of their use in the educational process is experimentally verified.